2014
DOI: 10.1021/jo500799j
|View full text |Cite
|
Sign up to set email alerts
|

Morita–Baylis–Hillman Reaction: ESI-MS(/MS) Investigation with Charge Tags and Ionic Liquid Effect Origin Revealed by DFT Calculations

Abstract: The use of a charge-tagged acrylate derivative bearing an imidazolium tag to study the Morita-Baylis-Hillman reaction via ESI-MS(/MS) monitoring and the effect of such tag (imidazolium cations and ion pairs) over TSs is described. The ionic nature of the substrate was meant to facilitate ESI transfer to the gas phase for direct mass spectrometric analysis. The detection and characterization of charged intermediates has suggested major reaction pathways. DFT calculations considering the effect of a polar and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 82 publications
2
24
0
5
Order By: Relevance
“…Fig. 4 indicates therefore that styrene polymerization starts with the formation of a key styrene chloronium cation which [30][31][32] and, more recently, by us [33]. Interestingly, the Schulz-Flory distributions for polystyrene produced with BMI.Fe 2 Cl 7 as the catalyst pointed to two or three active catalytic species (Table 4), hence the ESI-MS(/MS) data was in accordance with this prediction.…”
Section: Bmiclsupporting
confidence: 74%
“…Fig. 4 indicates therefore that styrene polymerization starts with the formation of a key styrene chloronium cation which [30][31][32] and, more recently, by us [33]. Interestingly, the Schulz-Flory distributions for polystyrene produced with BMI.Fe 2 Cl 7 as the catalyst pointed to two or three active catalytic species (Table 4), hence the ESI-MS(/MS) data was in accordance with this prediction.…”
Section: Bmiclsupporting
confidence: 74%
“…Reaction scheme for the Morita-Baylis-Hillman reaction. The intermediates 2, 3, 4,and 5 have been identified by ESI-MS. [36] Angewandte Chemie by ESI-MS they detected several of the expected intermediates.I np articular,i no ffline nano-electrospray experiments with UV and NMR quantification they demonstrated that the reaction rate is improved in the spray droplets.…”
Section: Mapping Routes Of Multicomponent Reactionsmentioning
confidence: 98%
“…Recently,N eto and co-workers published ar eport on the MBH reaction, and they described the use of an imidazolium-based charged acrylate derivative as ar eactant. [36] This approach, which was aimed at improving ESI-MS detection of the intermediates,a llowed characterization of transient zwitterionic species and noncovalent adducts.I np articular they identified thiourea-containing derivatives which are responsible for the enhanced reaction rate observed when using thiourea ( Figure 5). Thet wo hydrogen-bonding interactions of thiourea with the acrylate derivative are responsible for the noncovalent organocatalysis.…”
Section: Mapping Routes Of Multicomponent Reactionsmentioning
confidence: 99%
“…Neben diesen MBH‐Studien, in denen erstmals entscheidende Zwischenstufen abgefangen und charakterisiert wurden, befasste sich eine Reihe von weiteren ESI‐MS‐Untersuchungen mit noch offenen mechanistischen Fragen bei der MBH‐Umsetzung. Hierzu verwendeten Neto und Mitarbeiter in einer neueren Studie ein geladenes Imidazolium‐Acrylsäurederivat als Reaktionspartner . Während die Autoren ursprünglich den Nachweis von Intermediaten durch ESI‐MS verbessern wollten, charakterisierten sie transiente zwitterionische Spezies und nichtkovalente Addukte.…”
Section: Mehrkomponentenreaktionenunclassified